Monitoring A Grid Connected PV Power Generation System with Labview - Bayrak, Gokay; Cebeci, Mehmet (Ieee, 2013)
Generating power with solar cells has been developed rapidly in recent years and in parallel of photovoltaic (PV) systems becoming widespread in power generation systems in all around the world, there have been some requirements about integration of PV power generation systems into the traditional generation systems. One of these requirements will be monitoring PV generation systems and also adopting PV power generation systems to the present power system is another significant subject. In this study, a monitoring system was introduced for developed PV power generation system in the laboratory with Labview by using its useful and effective tools. 1.2 kWp grid connected PV system was used as a PV power generation system and NI USB-6221 data acquisition (DAQ) card and developed electrical measurement circuits were used for monitoring the PV system. Parameters and parameter changes at current, voltage and generated power in PV system acquired from the system and these parameters were monitored in real time thanks to Labview DAQ card. Output voltage, output current and power generated from the PV system were also monitored with developed Labview software. All the experimental results obtained from the PV power generation system were explained detailed in the paper. Proposed real time monitoring system is robust and reliable for grid connected PV power generating systems and it can be adapted easily to other PV generation systems.
International Conference on Renewable Energy Research and Applications (ICRERA) -- OCT 20-23, 2013 -- Madrid, SPAIN
Keywords: grid connected PV system; real time monitoring; data acquisition